Improving the environmental hazard scores metric for solvent mixtures containing carbon dioxide for chromatographic separations. Issue 11 (6th May 2022) - Gray, Rebekah; Fitch, Brian; Aurigemma, Christine; Hicks, Michael B.; Beres, Martin; Farrell, William; Olesik, Susan V.
Abstract : Quantifying the greenness of chromatographic separations using CO2 in the mobile phase. Abstract : Conventional liquid chromatography (HPLC) annually utilizes large quantities of organic solvents, such as methanol and acetonitrile, and reduction in the use of these hazardous solvents could lead to greener separation methods. Supercritical fluid chromatography (SFC) has been proposed as an alternative to traditional liquid chromatography primarily due to its use of carbon dioxide, which is a non-toxic, non-flammable solvent that can readily be recycled, if desired. Recently, the American Chemical Society Green Chemistry Institute Pharmaceutical Roundtable developed the Analytical Method Greenness Score (AMGS) calculator to assess the greenness of several different separation techniques, including SFC, based on instrumental energy, solvent energy, solvent environmental, health, and safety (EHS) scores, and solvent consumption. While this calculator is a highly useful tool, several modifications are needed to accurately assess the greenness of SFC, particularly regarding how CO2 is accounted for in the AMGS calculator. For instance, the AMGS calculator estimates the EHS score for CO2 to be the same as water due to its low toxicity. In this work, EHS scores for CO2 that account for instrument operating pressures and temperatures were determined for the first time and were found to be significantly different than those of water. In addition, the density of CO2 used in the AMGS calculator was altered to more accurately reflect the state of CO2 used in SFC. Furthermore, the compositions of alcohol–CO2 –air mixtures that result from leaks and their corresponding hazard times were determined. This new data can be readily incorporated in the AMGS calculator that is currently in use by most major pharmaceutical separations teams. Overall, this work aims to provide modifications to the existing AMGS calculator leading to a more accurate assessment of the greenness of CO2 -containing mobile phases in chromatographic applications specific to the pharmaceutical industry.